स्वप्नदृष्टि महाकाव्यमा अङ्गी रस - Chhetri, Khopiram Oli (Haimaprabha, 2025)
The main problem of this research work is that rasa is present as angi rasa in Ram Prasad Gyawali’s epic poem Swapnadristhi. The objective is to determine how a rasa has attained maturity as angi rasa. For this work, Swapnadristhi has been selected from among many other poems of Gyawali through random sampling method and the necessary materials for determining the use of rasa in Swapnadristhi have been collected from library work. Facts have been collected using Swapnadristhi as the primary source. Bharata, Vishwanath and Jagannath’s beliefs on rasa, criticism on dream vision, analysis and researched materials are used as secondary sources. Under the qualitative research framework, this article uses the analytical research method, on the basis of the development of Rasa. It has been concluded that Bir Rasa is the major Rasa and Shanta, Shringar, Humor, Raudra, Awada, Terrifying, Karuna, Vibhatsa Rasa come as the supporting Rasa to the Bir Rasa. Although the opposing Rasas of Bir Rasa are peaceful, humorous, and terrifying, this research becomes original and innovative because it shows new facts about how the opposing Rasa can also be used as a supporting Rasa in this epic.